Age estimation from ossification of sternum and true ribs using 3D post-mortem CT images in a Japanese population - Tawachai Monum (2020)
© 2019 Elsevier B.V. Age estimation of cadavers from post-mortem “chest plate” using conventional radiography, which involves radiographic assessment of ossification around the sternum and rib ends, has been evaluated without fruitful results. This study examined the value of images of the chest plate obtained by three-dimensional post-mortem CT for estimation of age at time of death in a Japanese population. Five chest plate ossification scores were evaluated in 320 subjects, including ossification of the first costal cartilage (OF), ossification of the second to seventh costal cartilages at the rib (OR) and sternal (OS) ends, fusion of the manubriosternal joint (FM), and fusion of the xiphisternal joint (FX). OS was found to have the highest correlation with age while FM had no significant correlation. The best composite score for age estimation was the summative score for both sides of the OS and the right side of the OF and FX, for which the coefficient of determination (R2) and the standard error of estimation (SEE) were 0.608 and 12.44 years, respectively, for men and 0.590 and 14.65 years for women. The accuracy of the model was tested in a further 26 male and 24 female subjects, and the accuracy rate within the first SEE was 57.69% and 70.83%, respectively. This rapid and non-invasive method of age estimation in the chest plate area is superior to conventional methods and could be useful for estimation of age at time of death in the Japanese population.